Public Libraries and Houseless Patrons: A Defense of Libraries as Social Services Providers - Bolton, Lisa (MacEwan University Student eJournal, 2023)
Public libraries play a vital role in their communities as information providers offering programs ranging from early literacy programs for infants to resume help and career coaching for adults re-entering the workforce. As complex socioeconomic realities continue to evolve around Covid-19, and government and non-profit agencies appear limited in the scope of assistance they provide, libraries offer critical services for a variety of needs shouldered by the marginalized in their communities. Specifically, public libraries support houseless patrons through a variety of initiatives ranging from employing on-site social workers to providing programs specific to adult literacy and the development of social connections. Consequently, public libraries show a rare commitment among public establishments to serve all members of their community with dignity and equality.